Differential diagnosis between spiritual experiences and mental disorders of religious content (Archives of Clinical Psychiatry, 2009)
CONTEXT: Spiritual experiences can be confused with psychotic and dissociative symptoms, providing it is frequently a challenge for the differential diagnosis. OBJECTIVE:To identify criteria to allow the elaboration of a differential diagnosis between spiritual experiences and psychotic and dissociative disorders. METHODS:It was made a wide revision in the literature about the theme, in which 135 articles identified in the research in PubMed were examined. RESULTS:Nine criteria were identified for a greater agreement among the researchers that could indicate an appropriate distinction between spiritual experiences and psychotic and dissociative disorders. They are, in relation to the lived experience: lack of psychological suffering, absence of social and occupational impairments, short duration of the experience, critical attitude (to have doubts about the reality of the experience), compatibility with the patient's cultural or religious group, no co-morbidities, control over the experience, personal growth along the time and an attitude to help the other ones. The presence of those conditions suggests a not pathological spiritual experience, but, on the other hand, there is lack of well controlled studies testing these criteria. DISCUSSION: These criteria proposed in the literature, although reaching an expressive consensus among different researchers, still needs to be tested empirically, and methodological directions for future researches about this theme are suggested.